2019
DOI: 10.1186/s12943-019-0948-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated secretion of LOXL4 promotes hepatocellular carcinoma cell invasion and metastasis

Abstract: BackgroundLysyl oxidase-like 4 (LOXL4) has been found to be dysregulated in several human malignancies, including hepatocellular carcinoma (HCC). However, the role of LOXL4 in HCC progression remains largely unclear. In this study, we investigated the clinical significance and biological involvement of LOXL4 in the progression of HCC.MethodsLOXL4 expression was measured in HCC tissues and cell lines. Overexpression, shRNA-mediated knockdown, recombinant human LOXL4 (rhLOXL4), and deletion mutants were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
162
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 67 publications
6
162
1
Order By: Relevance
“…Accumulating evidence has indicated that HCCderived exosomes may play important roles in tumor angiogenesis by delivering microRNA, proteins and other cargoes to communicate with cells in TME and remold TME [34][35][36]. Here, we also found that HCC cellsecreted exosomes promoted the angiogenesis of HUVECs (Additional file 7: Figure S4).…”
Section: Discussionsupporting
confidence: 63%
“…Accumulating evidence has indicated that HCCderived exosomes may play important roles in tumor angiogenesis by delivering microRNA, proteins and other cargoes to communicate with cells in TME and remold TME [34][35][36]. Here, we also found that HCC cellsecreted exosomes promoted the angiogenesis of HUVECs (Additional file 7: Figure S4).…”
Section: Discussionsupporting
confidence: 63%
“…Substantial evidence, including that in this study, implicates LOXL4 as a target that contributes to both vascular and fibrotic processes associated with ECM synthesis and remodeling . Most recently, LOXL4 was found to promote cancer growth and metastasis by regulating cell cycle mediators . Therefore, antibody therapies directed against LOXL4 may not merely target antifibrotic pathways but may also modulate pathways associated with anti‐vasculopathic phenotypes, which regulate the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 58%
“…These vesicular structures are highly stable and are small enough to penetrate into and interact with different tissues. Exosomes are involved in key physiological processes such as cell-to-cell communications [3], proliferation [4], migration [5], invasion [6], angiogenesis [7], and tumor growth [8] through the horizontal transfer of RNA and proteins.…”
Section: Introductionmentioning
confidence: 99%